The study of social relations of babies in day care: an interdisciplinary approach - Ângela Maria Scalabrin Coutinho (Universidade Federal de Santa Catarina, 2009)
This communication aims to present some thoughts on production in the field of sociology and education of babies and their social relations in the nursery, and the possibilities of dialogue between different fields of knowledge in the interdisciplinary study of issues such as related to children and their childhoods. To do so, takes as a reference for doctoral research in progress which aims to investigate the relationship of socio babies, to get information for the training of teachers of early childhood education. Some questions that guide the study are: The capacity allocated to children requires further knowledge of their modes of organization from the analysis of relationships between infants, given the way its structure interactions and modes of communication, so that measure the independent meanings they produce, already announced by other studies, are consolidated in symbolic systems standard? The extent to which babies reinterpret the societal culture in their social actions? What relationships are established within the interactions between the pairs? Think of how specific social action of the babies from the dialogue with the sociology of education seems to us a possibility to get codes for the training courses for teachers, which often exclude the specificities of their curricula of educational processes with children and small, theme also quite absent in the production of theoretical areas.